Effect of solvent, reaction time on morphology of Cu2ZnSnS4 (CZTS) nanoparticles and its application in Dye Sensitized Solar Cells. (2016) - Mokurala, Krishnaiah; Kamble, Anvita; Bathina, Chaitanya; Bhargava, Parag; Mallick, Sudhanshu
Abstract: Cu2 ZnSnS4 (CZTS) nanoparticles were prepared by a wet chemical process using different solvents like deionized water (DW) and ethylene glycol (EG). Physical characterization of the as-synthesized CZTS nanoparticles was confirmed by XRD and FEG-TEM. Prepared homogenous slurry was coated on FTO substrate to obtain CZTS film by inexpensive drop casting technique. Subsequently, the films were sulfurized at 550°C for 30 min. Physical and electrochemical catalytic activity of the sulfurized films were studied. Sulfurized CZTS films were utilized as an alternative counter electrode (CE) for dye sensitized solar cells (DSSCs) instead of the Pt based CE. DSSCs fabricated with CZTS nanorods, nanoflowers with sheets and spherical nanoparticles as CE material demonstrated an efficiency of 7.8%, 7.5% and 7.4%, respectively. Conventionally used Pt based CE exhibited an efficiency of 8.2%.